Zeichentragende Artefakte im sakralen Raum Zwischen Präsenz und UnSichtbarkeit - Keil, Wilfried E.; Kiyanrad, Sarah; Theis, Christoffer; Willer, Laura (Materiale Textkulturen, 2018)
Sign-bearing artifacts are immanent elements of sacred spaces in many cultures. Often, one encounters a phenomenon there that might be described as deliberate "invisibility," the conscious "concealment" of artefacts and writing. The volume examines this interplay of presence and invisibility using the example of sign-bearing artefacts in sacral spaces in various religions in the Near East and Europe.